Prevalence of toxigenic Clostridium difficile in hospitalized patients in the southwestern province of Saudi Arabia: Confirmation using the GeneXpert analysis - Nader Kameli; Vinod Kumar Basode; Ahmed Abdulhaq; Mohammed Uthman A. Alamoudi; Khalid Amaash Mohammed Zain; Ahmad Hassn Ghzwani (Libyan Journal of Medicine, 2024)
Clostridium difficile (Clostridioides difficile) is a leading cause of nosocomial infections in hospitalized patients worldwide. Stool samples were collected from 112 inpatients admitted to different hospitals and were screened for C. difficile GDH + toxin A + B by immunoassay, and all positive samples by immunoassay were processed for molecular detection of C. difficile using the GeneXpert assay. C. difficile strains were detected in 12 (10.71%) out of 112 stool samples using the GDH + toxin A + B immunoassay method and toxigenic C. difficile was confirmed in 5 stool samples using the GeneXpert molecular assay. C. difficile strains were also detected in 7 (8.97%) out of 78 stool samples from intensive care unit patients, 3 (25%) out of 12 stool samples from internal medicine ward patients, 1 (11.11%) out of 9 stool samples from surgery ward patients, and 1 (10%) out of 10 stool samples from isolation ward patients using the GDH + toxin A + B immunoassay method and the toxigenic C. difficile strain was confirmed in 1, 2, 1, and 1 stool samples, respectively, using the GeneXpert molecular assay. Toxigenic C. difficile was confirmed in patients at 4 (51.14%) out of 7 hospitals. In the present study, we also analyzed the clinical information of patients with C. difficile-positive stool samples who were receiving one or more antibiotics during hospitalization. The binary toxin gene (cdt), the tcdC gene, and the C. difficile strain polymerase chain reaction (PCR) ribotype 027 were not detected using the GeneXpert molecular assay among 12 C. difficile-positive samples by immunoassay. This study should aid in the prevention of unnecessary empiric therapy and increase the understanding of the toxigenic C. difficile burden on the healthcare system in the southwestern province of Saudi Arabia.